Kudliński i Osterwa. Sprawa „Hamleta” - Sobiecka , Anna (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2018)
This paper is dedicated to the theatrical novel by Tadeusz Kudliński 'Świętokradca' (1947), in which a fictional dialogue between the author of the novel and the performance concept of Shakespeare’s 'Hamlet' by Juliusz Osterwa is being held. Analysis of the novel, in which a metatextual frame is included as well, is confronted with earlier considerations of Wanda Świątkowska, who had conducted a close analysis of Juliusz Osterwa’s 'Hamlet', considering his personal and professional relationship with Tadeusz Kudliński, too. The novel 'Świętokradca' released in the year of Osterwa’s death, not only provides another interpretation of Hamlet, but also makes an attempt to combine both Kudliński’s and Osterwa’s concepts.